Evidence Brief: Improving End-of-life Communication, Decision-making and Care in Ontario - Gauvin, François-Pierre; Lavis, JN (My University, 2013)
An assessment of what is known about problems related to end-of-life communication, decision-making and care, options for addressing these problems, and key implementation considerations. The evidence brief was an input to a stake holder dialogue on the topic of improving end-of-life communication, decision-making and care in Ontario.
Keywords: end-of-life; communication; decision-making; Ontario